1998
DOI: 10.1038/bjc.1998.579
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of recombinant human erythropoietin in the prevention of chemotherapy-induced anaemia

Abstract: Summary Recombinant human erythropoietin (rHuEPO) has been advocated for the treatment of anaemia in patients submitted to cancer chemotherapy. We used decision analysis to compare the cost-effectiveness of rHuEPO supplemented with red blood cell (RBC) transfusions with conventional treatment with RBC transfusions alone. At Anaemia is a frequent complication in patients with cancer receiving cytotoxic chemotherapy. It impairs patients' physical capabilities and subjective sense of well-being, diminishing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 30 publications
1
42
0
1
Order By: Relevance
“…Three cost-utility studies [114][115][116] included in the systematic review reported by Wilson and colleagues 2 are also included in the update review and are hence not reported here. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three cost-utility studies [114][115][116] included in the systematic review reported by Wilson and colleagues 2 are also included in the update review and are hence not reported here. …”
Section: Resultsmentioning
confidence: 99%
“…Full texts were retrieved for 44 citations (the remainder being excluded as irrelevant on the basis of title and/or abstract). Five studies [114][115][116][117][118] were included following full-text screening (the remainder generally being excluded for not considering both costs and benefits). Figure 24 provides the study flow diagram for the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study in which EPO was actually used for treatment, a higher cost ratio of 3.9 was suggested [41]. In a study of cost-effectiveness of recombinant human EPO (rHuEPO) in the prevention of chemotherapy-induced anaemia, Barosi et al [40] estimated that the cost of rHuEPO was always greater than $100 000 per quality-adjusted life year (QALY). They concluded that according to current use, rHuEPO is not cost-effective in the treatment of chemotherapy-induced anaemia.…”
Section: Costs Of Erythropoietins For Treatment Of Anaemiamentioning
confidence: 99%